2022
DOI: 10.3390/ijerph192315900
|View full text |Cite
|
Sign up to set email alerts
|

Oral-Health-Related Self-Efficacy among the Elderly Population in Riyadh, Saudi Arabia

Abstract: Oral health self-efficacy is a fundamental determinant of behavioral changes among elderly patients. Objective: To assess the oral self-efficacy among the Saudi population aged 65 years old and above in Riyadh, Saudi Arabia. Methodology: This was a cross-sectional survey conducted on elderly individuals in Riyadh. An Arabic version of the Geriatric Self-Efficacy Scale for Oral Health (GSEOH) was administered to all participants. The dependent variables included oral function, oral hygiene habits, and dental vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Vozza et al 34 reported that decreased chewing strength might lead to softer foods for feeding, leading to malnutrition, inadequate protein intake or increased body mass index. Kshetrimayum et al, in their study in India, Anweigi et al, in their research in Saudi Arabia, declared that there is a critical link between oral health, nutrition and quality of life in the elderly 35,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vozza et al 34 reported that decreased chewing strength might lead to softer foods for feeding, leading to malnutrition, inadequate protein intake or increased body mass index. Kshetrimayum et al, in their study in India, Anweigi et al, in their research in Saudi Arabia, declared that there is a critical link between oral health, nutrition and quality of life in the elderly 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…Kshetrimayum et al, in their study in India, Anweigi et al, in their research in Saudi Arabia, declared that there is a critical link between oral health, nutrition and quality of life in the elderly. 35,36 The study has some limitations due to the absence of a representative sample. Patients were recruited at a dental and medical clinic to expand the number of patients and to enable the selection of patients undergoing different prosthetic treatments.…”
Section: Erdinç Andmentioning
confidence: 99%
“…In China, more and more elderly patients require tooth restorations owing to the intensification of the aging trend [ 1 ]. Moreover, improved living standards and increased public health awareness have led to a surge in the demand for high-quality oral restorations in elderly patients with missing teeth [ 2 ]. In recent years, implant restoration has gradually become the first choice for restoring missing teeth in elderly patients owing to its properties, such as improved comfort and masticatory efficiency [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since strengthening perceived self-efficacy is a well-established mechanism for improving health and health-related behaviors [ 7 , 8 , 11 , 23 , 24 ] in a wide variety of diseases [ 12 , 25 , 26 ], improving OH-SE might also be a promising approach in the context of oral health. Recent research has also documented a protective effect of more pronounced OH-SE on oral health, suggesting that strengthening OH-SE might reduce oral health-related problems in the future [ 3 , 13 , 14 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Measuring OH-SE comes with some challenges, as related scales mostly address specific behaviors (e.g. toothbrushing, flossing) or aim at capturing this construct in specific populations [ 3 , 13 , 14 , 27 , 31 ]. Because these measurements seemed inappropriate for our population, we followed Bandura’s original definition [ 7 ] and developed a new question (see methods section) to capture OH-SE.…”
Section: Introductionmentioning
confidence: 99%